Establishment of in vitro regeneration protocol of Gerbera jamesonii from different explants - Rahman, Md. Minhazur (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2016